Endo-perio lesions: diagnosis and interdisciplinary treatment options - Dakó Timea; Lazăr Ana Petra; Bică Cristina Ioana; Lazăr Luminița ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2020)
About 50% of tooth loss is caused by either endodontic infection, periodontal disease or the combination of the two in the form on endo-perio lesions (EPL). Combined EPL develop due to the intimate anatomic and functional relation between endodontic and periodontal tissues. Both the pulp and periodontium share the same embryologic and anatomic origin. The various pathways connecting the two, added up to the extremely alike microorganisms in both illnesses' etiology, create a complex condition in which interdisciplinary approach is required. Despite numerous decades of literature describing these lesions, they remain a continuous challenge for practitioners in both diagnosing and managing. The purpose of this article is to present a comprehensive review of various aspects of the combined EPL and to emphasize the importance of making a correct diagnosis and adopting the appropriate treatment method in the management of these challenging situations.